Magnetic-responsive triple shape memory polymer from bio-based benzoxazine/urethane polymer alloys with iron oxide nanoparticles - Kullanard Ruenpanya; Phattarin Mora; Panagiotis Karagiannidis; Kittipon Bunyanuwat; Sarawut Rimdusit (Advanced Industrial and Engineering Polymer Research)
Novel magnetic-responsive triple shape memory polymers (SMPs) derived from bio-based benzoxazine-urethane (V-fa/PU) polymer alloys containing iron oxide nanoparticles (Fe3O4 NPs) were developed in this work. Shape memory effect and curing behavior of the alloys were investigated at various bio-based PU contents. The polymerization of V-fa/PU polymer alloys with a heterogeneous network generated a broad glass transition temperature, which is a crucial feature for the development of triple SMPs. The influence of Fe3O4 NPs incorporation into the polymer nanocomposites on the SMP performance triggered by magnetic fields was also investigated. It was found that the addition of Fe3O4 NPs can enhance the dynamic mechanical properties and magnetic characteristics of the V-fa/PU polymer alloys thanks to the superparamagnetic property of Fe3O4 NPs. Moreover, the performance of the SMPs based on V-fa/PU polymer nanocomposites filled with Fe3O4 NPs showed high shape fixity of up to 98%, a shape recovery of 98%, and a recovering time of 8 s. Furthermore, bio-based V-fa/PU polymer alloys containing Fe3O4 NPs were developed as magnetic responsive triple SMPs with shape fixity in the range of 95–97% and shape recovery in the range of 85–95%. The results suggested that magnetic responsive triple SMPs from bio-based V-fa/PU polymer alloys filled with Fe3O4 NPs are promising candidate for advanced applications.